The Role and Features of Cross-sectoral Collaboration in Disinformation Governance - Kasparaitė, Rimgailė (Information & Media, 2026)
Disinformation constitutes a multifaceted challenge within the contemporary digital environment. Although governments, digital platforms, media organizations, and civil society actors have introduced regulatory, technological, and educational responses, these initiatives remain fragmented and focus on sector-specific responsibilities. This conceptual article explores the possibility that, although necessary, such approaches are more likely to conflict with one another when addressing disinformation as a complex and systemic issue. It develops a conceptual framework that redefines disinformation governance as a matter of cross-sectoral collaboration rather than divergent and competing strategies. Cross-sector collaboration is theorized as an institutional mechanism for constituting and sustaining collective agency, defined as the capacity of a group or network to operate as a unified actor, making decisions or undertaking coordinated actions. The analysis identifies the necessary preconditions for cross-sectoral collaboration, including identifying competencies and resources, reconciling interests, establishing common definitions of the issue, ensuring procedural transparency, fostering mutual understanding, building trust, and shared leadership. These are followed by the development of established norms of communication, which serve as foundational conditions for joint knowledge production and decision-making, both of which are central to the governance of complex societal challenges.
Keywords: disinformation; governance; digital communication; cross-sectoral collaboration